2006
DOI: 10.3201/eid1708.060327
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia felis inXenopsylla cheopis, Java, Indonesia

Abstract: Rickettsia typhi and R. felis, etiologic agents of murine typhus and fleaborne spotted fever, respectively, were detected in Oriental rat fleas (Xenopsylla cheopis) collected from rodents and shrews in Java, Indonesia. We describe the first evidence of R. felis in Indonesia and naturally occurring R. felis in Oriental rat fleas.M urine typhus (endemic typhus, fleaborne typhus), caused by Rickettsia typhi, is transmitted to humans by infected fleas and is relatively common wherever susceptible rodent hosts resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 14 publications
1
25
0
4
Order By: Relevance
“…With a larger sample of X. cheopis and other flea species, it would be of interest to test for the presence of coinfection with R. felis and R. typhi in the same positive fleas, because it was previously reported in experimental works 42 and under natural conditions. 22,43,44 The analysis of the sequence electropherograms showed lack of ambiguity in the nucleotide assignments for all samples included. Because the PCR products were derived from pools in which several members could be positive, the clean sequence reads suggest that the amplified fragments were highly conserved and/or that only one flea in each pool was positive for a single Rickettsia.…”
Section: Discussionmentioning
confidence: 99%
“…With a larger sample of X. cheopis and other flea species, it would be of interest to test for the presence of coinfection with R. felis and R. typhi in the same positive fleas, because it was previously reported in experimental works 42 and under natural conditions. 22,43,44 The analysis of the sequence electropherograms showed lack of ambiguity in the nucleotide assignments for all samples included. Because the PCR products were derived from pools in which several members could be positive, the clean sequence reads suggest that the amplified fragments were highly conserved and/or that only one flea in each pool was positive for a single Rickettsia.…”
Section: Discussionmentioning
confidence: 99%
“…R. felis infections produce a clinical syndrome similar to that of murine typhus. 35 Given the clinical similarities, some authors believe that previously reported outbreaks of murine typhus infections may have been caused by the more recently recognized R. felis.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…32,33 Infection of rat flea Xenopsylla cheopis with R. felis has also been found in Indonesia, which increases the possibility of human infections with R. felis in the region, although no clinical case has been reported to date. 35,37 Ectoparasite field surveys of villages in Laos and Malaysian Borneo of domestic animals also showed significantly high overall R. felis DNA detection rates of 76.6% and 74.4%, respectively. 36 However, in contrast, another study in peninsula Malaysia showed a lower rate (2.9%) of R. felis DNA detection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Human and animal infections of R. felis and bartonellae have been reported in Southeast Asia. 16,[22][23][24] This study is the second study in Southeast Asia that investigated the prevalence of R. felis and bartonellae in flea samples. Compared with the previous study, 16 a larger number of fleas examined in this study were positive for B. henselae and B. clarridgeiae .…”
mentioning
confidence: 99%